2005
DOI: 10.1063/1.2152111
|View full text |Cite
|
Sign up to set email alerts
|

Role of structural defects on exchange bias in the epitaxial CoO∕Co system

Abstract: We have studied the influence of non-magnetic defects throughout the antiferromagnet Co 1-y O on the exchange bias (EB) in epitaxially grown Co 1-y O/Co bilayers. These defects are either substitutional or structural (twin boundaries and surface morphology) which both lead to an increase of the EB field. We find a dominance of twin boundaries over surface morphology (roughness) in enhancing EB which is consistent with the domain state model for exchange bias. In contrast, the crystal orientation of the Co 1-y … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 12 publications
3
24
0
Order By: Relevance
“…[18][19][20][21][22][23][24] In pioneering work, it was shown that the deliberate introduction of non-magnetic structural-defects into highly-crystalline epitaxial thin films of Co/CoO via dilution of the antiferromagnet with non-magnetic atoms such as Zn, 20) or by deliberate crystal twinning, 21) enhanced exchange bias by assisting the formation of dilute-antiferromagnetic thermal remnant magnetization, 22,23) in accordance with the predictions of the atomistic domain state model (DSM). 24,25) It is worth noting that in that body of work, the absolute maximum exchange bias recorded for such MBE-grown $20 nm thick Co/CoO films was 700 Oe at 5 K, 21) whereas all of our thicker $60 nm sputtered films have a comparable exchange bias at 200 K, suggesting a higher blocking temperature and interfacial energy. The exchange bias found for the samples studied in this work is similar to the result found for epitaxial films Co where deliberate oxygen ion-implantation was performed to form Co/CoO nanocomposites (H ex $ 400 Oe), although there higher ion-beam energies were used (60 keV) presumably resulting in a different overall microstructure.…”
Section: Discussionmentioning
confidence: 76%
“…[18][19][20][21][22][23][24] In pioneering work, it was shown that the deliberate introduction of non-magnetic structural-defects into highly-crystalline epitaxial thin films of Co/CoO via dilution of the antiferromagnet with non-magnetic atoms such as Zn, 20) or by deliberate crystal twinning, 21) enhanced exchange bias by assisting the formation of dilute-antiferromagnetic thermal remnant magnetization, 22,23) in accordance with the predictions of the atomistic domain state model (DSM). 24,25) It is worth noting that in that body of work, the absolute maximum exchange bias recorded for such MBE-grown $20 nm thick Co/CoO films was 700 Oe at 5 K, 21) whereas all of our thicker $60 nm sputtered films have a comparable exchange bias at 200 K, suggesting a higher blocking temperature and interfacial energy. The exchange bias found for the samples studied in this work is similar to the result found for epitaxial films Co where deliberate oxygen ion-implantation was performed to form Co/CoO nanocomposites (H ex $ 400 Oe), although there higher ion-beam energies were used (60 keV) presumably resulting in a different overall microstructure.…”
Section: Discussionmentioning
confidence: 76%
“…The formation of the DS depends on the degree of structural order in the AFM. Therefore, different kinds of structural and compositional defects 10,22 acting as pinning centers for the AFM domain walls contribute to the creation of the AFM DS. Since the epitaxial growth of ͑110͒ Fe 50 Mn 50 was observed to be superior compared to the epitaxial growth of ͑001͒ Fe 50 Mn 50 , we expect less defects in the ͑110͒ Fe 50 Mn 50 as compared to the ͑001͒ orientation.…”
Section: Resultsmentioning
confidence: 99%
“…3͑a͔͒ main nucleation and wall propagation have been assigned in the vicinity of H 1 . 21 The DS model 8,10 for EB considers the presence of defects 22 throughout the finite AFM lattice, leading to the formation of AFM domains. Consequently, an irreversible DS magnetization develops in the AFM during the field cooling.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, based on the domain state model, some reports have reported that the magnitude of the EB field (H E ) could be controlled by intentionally diluting the FM phase [10], AFM phase [11,12] or introducing non-magnetic defects [13,14] in the AFM phase. A distinct enhancement of H E (more than 60%) with a Cu dilution of only 5% is observed in the IrMn layer [15].…”
Section: Introductionmentioning
confidence: 99%